Observation of the [Lambda]0b→ J[psi]/[Xi]−K+ and [Xi]0b→ J/[psi][Xi]−π+ decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (The European physical journal. C, Particles and fields, 2025)
The first observation of the Ξ0b → J/ψΞ−π+ decay and the most precise measurement of the branching fraction of the Λ0b → J/ψΞ−K+ decay are reported, using proton-proton collision data from the LHCb experiment collected in 2016–2018 at a centre-of-mass energy of 13TeV, corresponding to an integrated luminosity of 5.4 fb−1. Using the Λ0b → J/ψΛ and Ξ−b → J/ψΞ− decays as normalisation channels, the ratios of branching fractions are measured to be B(Λ0b → J/ψΞ−K+) B(Λ0b → J/ψΛ) = (1.17 ± 0.14 ± 0.08) × 10−2 , B(Ξ0b → J/ψΞ−π+) B(Ξ−b → J/ψΞ−) = (11.9 ± 1.4 ± 0.6) × 10−2, where the first uncertainty is statistical and the second systematic.